MOORA METHOD (MULTI OBJECTIVE OPTIMIZATION ON THE BASIC OF RATIO ANALYSIS) FOR THE BEST MOTORCYCLE SELECTION RECOMMENDATIONS - Nurhayati (Cattleya Darmaya Fortuna, 2022)
Motorcycles are one of the main choices of transportation that are of interest to the public, especially Indonesia, because they are simple in size, fast and cheaper than other means of transportation such as cars. Now many emerging types / types of motorcycles complete with advantages and disadvantages. This of course will make it difficult for consumers to make the right choice, according to the desired criteria. To make it easier for buyers to choose the type of motorcycle that suits their wishes, a decision support system is designed to recommend the appropriate type of motorcycle. This system was built with accurate calculations using the MOORA (Multi Objective Optimization on The Basic of Ratio Analysis) method so that the accuracy of calculations is guaranteed which is applied using PHP MySQL software. With this system, buyers will have no difficulty choosing the type of motorbike that suits their needs and finances so that a comfortable and fast buying and selling process will be created.